The handbook of visual culture - Heywood, Ian; Sandywell, Barry (London ; New York : Berg, 2012)
Visual culture has become one of the most dynamic fields of scholarship, a reflection of how the study of human culture increasingly requires distinctively visual ways of thinking and methods of analysis. Bringing together leading international scholars to assess all aspects of visual culture, the Handbook aims to provide a comprehensive and authoritative overview of the subject. The Handbook embraces the extraordinary range of disciplines which now engage in the study of the visual - film and photography, television, fashion, visual arts, digital media, geography, philosophy, architecture, material culture, sociology, cultural studies and art history. Throughout, the Handbook is responsive to the cross-disciplinary nature of many of the key questions raised in visual culture around digitization, globalization, cyberculture, surveillance, spectacle, and the role of art. The Handbook guides readers new to the area, as well as experienced researchers, into the topics, issues and questions that have emerged in the study of visual culture since the start of the new millennium, conveying the boldness, excitement and vitality of the subject.
Historical and theoretical perspectives -- Art and visuality -- Aesthetics, politics and visual culture -- Practices and institutions of visual culture -- Developments in the field of visual culture.
Lisäpainokset: Paperback 2017, Bloomsbury. Reprintd 2021.
Keywords: Art and society; Communication and culture; Culture; Popular culture; Visual communication; Visual cultures; Visual perception; kulttuuri; kulttuurintutkimus; kuvallinen viestintä; mediakulttuuri; viestintä; viestintäkulttuuri; visuaalinen kulttuuri; Visuell kultur; handböcker